Bonding ability of adhesive resins to caries-affected and caries-infected dentin (Journal of Applied Oral Science, 2004)
Hybridized dentin permits dental treatments that were previously impossible with conventional techniques, opening new frontiers in modern adhesive dentistry. We have investigated the adhesive property of current bonding systems to caries-infected dentin by a microtensile bond strength test (µTBS) and transmission electron microscopy (TEM), and suggested that bonding resin could infiltrate into caries-infected dentin partially to embed carious bacteria within hybrid layers. We have named this concept of caries control as modified sealed restoration (MSR). On the other hand, Kuraray Medical Inc. (Tokyo, Japan) has developed an antibacterial adhesive system (ABF, now marketed in USA as Protect Bond). So as to evaluate the effectiveness of ABF on root caries control, we have examine the microtensile bond strengths (µTBS) of ABF to normal versus carious root dentin and the interfacial morphology by a scanning electron microscopy (SEM). ABF could form the hybrid-like structures by infiltrating into the surfaces of the root carious dentin, and the mean value of µTBS of ABF to root carious dentin was 23.0 MPa. These results suggested that MSR combined with ABF might be an advantageous minimal invasive therapy for root caries.